Analysis of Toll Queues by Micro-simulation: Results from a Case Study in Istanbul - Aksoy, Goker; Celikoglu, Hilmi Berk; Gedizlioglu, Ergun (Elsevier BV, 2014)
AbstractIn this study, using a microsimulation model, queues of Fatih Sultan Mehmet (FSM) Bridge toll booths are analyzed. Generally two queues form in the study area. First one is in front of the booths and the second one is after the booths, due to the existing bottleneck between the booths and the Bridge. Queue/delay performance of the system is analyzed incorporating the queuing theory. According to demand and service time of each server, queue may occur before the booths and/or before the bottleneck. The propagation of the second queue may overlap the first one because of the bottleneck capacity and for sure the increasing demand. Four different scenarios are simulated in order to evaluate capacity of the toll collectors and the bottleneck section. Some traffic management strategies are applied to improve the quality of service by decreasing delays and increasing capacities. In each scenario, average delay time per vehicle, average travel time, occupancy and speed data are obtained with microsimulation software, Vissim. Finally, optimum number of toll collectors is determined by seeking to minimize delays and maximize bottleneck capacity.
Keywords: traffic flow; toll booths; simulation; queueing theory